Coupling of emergent octahedral rotations to polarization in (K, Na)NbO3 ferroelectrics. Issue 1 (December 2017) - Levin, I.; Krayzman, V.; Cibin, G.; Tucker, M.; Eremenko, M.; Chapman, K.; Paul, R.
Abstract Perovskite potassium sodium niobates, K1−x Nax NbO3, are promising lead-free piezoelectrics. Their dielectric and piezoelectric characteristics peak nearx = 0.5, but the reasons for such property enhancement remain unclear. We addressed this uncertainty by analyzing changes in the local and average structures across thex = 0.5 composition, which have been determined using simultaneous Reverse Monte Carlo fitting of neutron and X-ray total-scattering data, potassium EXAFS, and diffuse-scattering patterns in electron diffraction. Within the A-sites, Na cations are found to be strongly off-centered along the polar axis as a result of oversized cube-octahedral cages determined by the larger K ions. These Na displacements promote off-centering of the neighboring Nb ions, so that the Curie temperature and spontaneous polarization remain largely unchanged with increasingx, despite the shrinking octahedral volumes. The enhancement of the properties nearx = 0.5 is attributed to an abrupt increase in the magnitude and probability of the short-range ordered octahedral rotations, which resembles the pre-transition behavior. These rotations reduce the bond tension around Na and effectively soften the short Na-O bond along the polar axis – an effect that is proposed to facilitate reorientation of the polarization as external electric field is applied.